Transcriptional analysis of metastatic uveal melanoma survival nominates NRP1 as a therapeutic target. Issue 1 (February 2021) - Bao, Riyue; Surriga, Oliver; Olson, Daniel J.; Allred, Jacob B.; Strand, Carrie A.; Zha, Yuanyuan; Carll, Timothy; Labadie, Brian W.; Bastos, Bruno R.; Butler, Marcus; Hogg, David; Musi, Elgilda; et al.
Abstract : Uveal melanoma is a rare form of melanoma with particularly poor outcomes in the metastatic setting. In contrast with cutaneous melanoma, uveal melanoma lacks BRAF mutations and demonstrates very low response rates to immune-checkpoint blockade. Our objectives were to study the transcriptomics of metastatic uveal melanoma with the intent of assessing gene pathways and potential molecular characteristics that might be nominated for further exploration as therapeutic targets. We initially analyzed transcriptional data from The Cancer Genome Atlas suggesting PI3K/mTOR and glycolysis as well as IL6 associating with poor survival. From tumor samples collected in a prospective phase II trial (A091201), we performed a transcriptional analysis of human metastatic uveal melanoma observing a novel role for epithelial-mesenchymal transition associating with survival. Specifically, we nominate and describe initial functional validation of neuropillin-1 from uveal melanoma cells as associated with poor survival and as a mediator of proliferation and migration for uveal melanoma in vitro . These results immediately nominate potential next steps in clinical research for patients with metastatic uveal melanoma. Abstract : Supplemental Digital Content is available in the text.